Identity and adulthood - Kakar, Sudhir (Delhi Oxford University Press, 1979)
A selection of papers discussed at a seminar held in Delhi in 1977 under the auspices of the Indian Council of Social Science Research.
Keywords: Life cycle, Human; Identity (Psychology) -- Congresses. -- India; Adulthood -- Congresses. -- India; Hindus -- Attitudes -- Congresses